Cybercrime and challenges in South Africa - Ehiane, Stanley; Olofinbiyi, Sogo Angel; Mkhize, Sazelo Michael (Palgrave Macmillan, 2023)
1. Introduction and Contextual Background of Cybercrime as an Emerging Phenomenon and Associated Challenges in Africa -- 2. The Evaluation of Cybercrime in South Africa: A review of the impact of Identify Theft Menace on the economy -- 3. Cybercrime in the Developing Nations: Internet as Means of Sex Trafficking in Africa -- 4. The Golden Trends of Cybersecurity and its Emerging Challenges in Africa -- 5. The scourge of ransomware: The cybercrime growth industry of the early 2020s -- 6. Cyberspace and Drug Trafficking in Africa -- 7. An exploratory study of the South African Police services (SAPS) systems in combating cybercrime -- 8. Human trafficking: A Dark Side of the Cyberspace -- 9. Human trafficking and cyberspace in South African -- 10. Electronic-Filing [Tax] Fraud in South Africa: Perceptive and Trends.